(untitled) (Journal of the College of Basic Education, 2022)
The case study of students applying for admission to the College of physical education and sports sciences is an important stage for future judgments, because physical fitness tests reflect the special status of students in the field of physical and abilities, and because these tests and measurements have a relationship to most activities, it is difficult not to specify their specifications and to put them in duplicate curricula for faculties of education Physical and Sports Science. Classification helps in the process of selecting the right student for the appropriate activity by codifying training loads in lessons. Hence the importance of research in the process of classifying applicants for admission to the faculties of physical education and sports sciences. Quite a small number of students and professors suffer from low levels of practical subjects that require special methodological care, and no additions or revisions have been made to the practical curricula, as they have been written for tens of years, and most teachers cannot exceed the weekly timings allocated for these lessons. Classification will help put students In independent groupings and even in private classes for the purpose of developing their performance. The research aims to classify school students applying for admission to the faculties of physical education and sports sciences according to the battery tests and measurements for admission into independent groups. The research sample consisted of (570 students) of male applicants for admission to the College of Physical Education and Sports Sciences for the academic year (2018-2019), and they represented (95%) of those applicants for admission. Five tests were conducted on them that measure the elements of physical fitness for different parts of the body, namely: 60 meter sprint (to measure the speed) Run 540 meters (to measure endurance) Long jump (to measure the explosive power of the legs) Sitting from prone position within a minute (to measure the length of the abdominal muscles) Pull on the bar for 15 seconds (to measure the speed characteristic of the arms) The sample was divided into (5 groups) based on the number of tests using the (Classify) classification method (K-Means Cluster). The researcher concluded: One group was characterized by three characteristics (speed, explosive power, abdominal muscles elongation, speed characteristic of the arms) and this group constituted only (11%) of the applicants. Two groups were distinguished as (general probity) only, and these two groups constitute (43%) of the applicants. Applicants for admission to the College of Physical Education and Sports Science do not constitute a society with physical fitness that qualifies them for admission, except by reducing the practical average of test results.